Evaluation of health status and meat quality of dumbo catfish Clarias gariepinus maintained using the biofloc system - Anang Fajrin; Nurbambang Priyo Utomo; Julie Ekasari; Sri Nuryati (Jurnal Akuakultur Indonesia)
This research aimed to evaluate the health status, growth performance, and meat quality of African catfish Clarias gariepinus maintained in biofloc and nonbiofloc systems. This study applied 3 treatments with 4 replications, i.e. K500 (control, a non-biofloc system at a fish stocking density of 500/m3), BF500 (biofloc system at a fish stocking density of 500/m3), and BF700 (biofloc system at a fish stocking density of 700 /m3). The initial body length and bodyweight of the fish used in this experiment were 10–12 cm and 10–12g, respectively. Feeding was done by using a commercial feed containing 29.76% protein content. The results showed that fish survival in treatments BF500 and BF700 were significantly different (P<0.05) from the control. The growth rate of African catfish in the control (K) was the lowest (3.64 ± 0.56%) among the treatments. The results of the organosensory test showed that the application of biofloc systems produced a higher quality of fish meat with a range value of 7–9 compared to that of the control with a range of 6–7. In conclusion, the application of biofloc systems could improve the fish health status, growth performance, and meat quality of African catfish.